Delmar's anatomy & physiology challenge CD-ROM (USA : Delmar Publishers, 1998)
The computer game that challenges your knowledge of anatomy and physiology
This CD-ROM is available at makmal Digital, Perpustakaan Dr. Abdul Latiff, KKL
Keywords: Anatomy; Physiology